Facilitatory Effect of an Applying Capsaicin-Containing Film on Initiation of Swallowing Reflex - KOBAYASHI, Yukio; MAEKAWA, Kyoko; MORI, Takayuki; EGUSA, Masahiko; MURATA, Naomichi; MIYAWAKI, Takuya; KANDA, Yuko; GOTO, Takuro (The Japanese Journal of Dysphagia Rehabilitation, 2013)
Objective:　Red pepper contains a large amount of capsaicin, which is known to have a swallowing reflex-stimulating effect. Capsaicin is considered to facilitate the release of substance P (SP) by sensory nerves in the pharynx into mucosal membranes, allowing the reflex to occur easily due to elevated SP concentration. Capsaicin-containing film or wafers are now commercially available, and are easily ingested by patients with dysphagia. The swallowing reflex-stimulating effect after ingestion, however, has not been fully investigated. Thus, the effects of capsaicin-containing film on swallowing and cough reflexes, and their influence on SP concentration in saliva were examined in this study.Methods:　A cross-over, double-blind study was performed in 17 male adults aged between 20 and 40 years, using capsaicin-containing (capsaicin content: 1.5 mg/film) and placebo film. The swallowing reflex and the cough reflex were evaluated 6 times every 10 min after ingestion with a baseline value at rest measured 10 min before ingestion of the film. The lag time of swallowing was measured in a simplified swallowing-induction test to evaluate the swallowing reflex. A cough test was conducted using 1% citrate saline solution to evaluate the cough reflex. In addition, the SP concentration in saliva, which was collected 10 min before, 10 and 20 min after ingestion, was measured with an ELISA kit. The control group ingested placebo film. The Freidman test and the Wilcoxon signed-rank test were used for statistical analysis.Results:　Compared with the control group, the lag time of swallowing in the capsaicin group became significantly different at 20 and 40 min after ingestion of capsaicin. By comparing with the baseline of the capsaicin group, swallowing reflex was shortened after 40 min. No significant differences were observed at other measurement points or in other evaluation items.Conclusion:　Ingestion of capsaicin-containing film was demonstrated to have a swallowing reflexstimulating effect at 40 min after ingestion.